Analisis Manajemen Risiko UMKM Nasi Goreng Nggo Anglo di Antapani - Riskiawati, Suci; Siti Kulsum, Reysa; Lestari, Trie Ayu (Universitas Serambi Mekkah, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia, especially in the culinary sector, are growing rapidly but are alsoinseparable from challenges and opportunities. This study aims to analyze the risk management of Nggo Anglo Fried Rice MSMEs in Antapani. The method used is a qualitative approach with data collection techniques through interviews with fried rice MSME owners and direct observation at the business location. The results showed that the most significant risks include market, financial, marketing, operational and legal risks. This research contributes to business actors, so that they can increase resilience and competitiveness in the market.